Предмет: Алгебра,
автор: Renatt
упростите выражение (sinL-cosL)в квадрате -1+4sin2L
Ответы
Автор ответа:
0
(sinl-cosl)^2 -1 +4sin2l= sin^2 l - 2sinl*cosl+cos^2 l -1 + 8sinl*cosl= sin^2 l + 6sinl*cosl+cos^2 l -1
или (sinl-cosl)^2 -1 +4sin2l= -2cos2l-1+4sin2l
или (sinl-cosl)^2 -1 +4sin2l= -2cos2l-1+4sin2l= 2 корня из 5 *(sin(2l+arctg -0,5)) -1
или (sinl-cosl)^2 -1 +4sin2l= sin^2 l - 2sinl*cosl+cos^2 l - 1+4sin2l = - 2sinl*cosl+4sin2l= 3 sin2l
Похожие вопросы
Предмет: Математика,
автор: dimakrivovcom
Предмет: Физика,
автор: vvdenvv5
Предмет: Алгебра,
автор: princess2586
Предмет: Алгебра,
автор: lindsi